Community acquired recurrent urinary tract infection caused by Pseudomonas aeruginosa in a public health institute in eastern india: A case report (Indian Journal of Case Reports, 2019)
Urinary tract infection (UTI) is common in childhood with no gender preponderance. Often the diagnosis is missed or cases are neglected, and improperly treated. Common pathogens in community-acquired UTI are Escherichia coli, K. pneumoniae and Proteus spp.P. aeruginosa is quite rare as auropathogen in the community. A case of recurrent UTI was encountered in our Urban Health Centre where an eight-year-old male child had presented with urgency and frequency of urination without fever for the last one year. His urine culture revealed infection with highly drug-resistant P. aeruginosa. A history of contact with a relative who died of urosepsis at home several months back was traced. This is a serious instance of the spread of deadly strains of the bacteria into the society posing a great threat to the community particularly the vulnerable group like children.